APLIKASI INFLOW CONTROL DEVICE (ICD) PADA SUMUR HORIZONTAL UNTUK MENANGANI WATER CONING - Anugrah Massewa, Dias
Inflow Control Device (ICD) is a completion tool which is added to the well and will be useful to optimize oil production. ICD works by stabilizing the flow and pressure drop, so the problems that can arise because of those will be resolved. The most important issue caused by unstable pressure drop are water coning and gas coning which can be prevented by the using of ICD. Horizontal well is used to get larger contact area between well and reservoir in order to increase oil production and life time of a field. Reservoir with the type of oil rim is a layer of thin reservoir that is filled with oil, accordingly the application of horizontal well is fit for this type of reservoir. By proper using, horizontal well will get good flow rate capability and decent sweep efficiency. The problem which occurred in horizontal well is the heel to toe effect phenomenon. It happened when the biggest friction from the heel is causing huge pressure drop along the well. Because of this occurrence, there will be inconsistency of pressure drop that will lead to water coning and gas coning for production well. In overcoming the problem, the application of ICD is a right solution to optimize the production. In this research, sensitivity test will be performed for the application of ICD in horizontal well by using reservoir modelling software. The type of reservoir which will be observed is oil rim reservoir with heterogeneous permeability. This research focuses on water coning problem, so the sensitivity test is analyzing the correlation between intensity and the diameter size of ICD with the ability to overcome water coning.